Defining Appropriate Curriculum for English Diploma Program - Dwi Wulandari (PAROLE: Journal of Linguistics and Education, 2021)
This study is aiming at looking at the appropriate curriculum for Diploma Program in English by focusing on the targetted competence and the unique feature of the program. As a vocational school, English diploma program is facing problems in defining its own characteristics. The so far  called diploma program is actually the shorthened term of the undergraduate English program with the absence of literary and linguistics related courses, and focused merely on the English skill learning. Although some practical skills other than English have been embedded in the curriculum, such as the additional courses in tourism and public relations, still the program missed the answer for its basic question; what the targetted competence and the unique feature of the program are. This research is done in trying to find the answer by doing both library research trying to take a look the ideal features of English Diploma programs, and interview trying to see the nature and the specific goal targetted by the management in handling the programs as well as the difficulties to match the present condition with the ideal one. The study reveals that some of English diploma programs may face the same issue of not being clear in targetting the competence as the vocational program, although some have found what is being idealized.